The Influence of Group Guidance Services with Simulation Game Techniques to Develop Self-Concept - Ramadhani, Siti Nabilla; Ismanto, Heri Saptadi; Lestari, Farikha Wahyu; Paramartha, Wayan Eka (Department of Guidance and Counseling, FIP, Undiksha, 2020)
This research is motivated by the lack of self-concept in students including the objectives to be achieved in this study are to grow and develop self-concept in class VIII students of SMP Negeri 6 Semarang. This type of research is quantitative. The population of this study were students of class VIII SMP Negeri 6 Semarang with a total of 224 students. The sample was taken 28 students consisting of 14 students from the control class and 14 students from the experimental class. The sampling technique was using proportionate random sampling. The data in this study were obtained through a psychological scale research instrument with a self-concept Likert scale that was modified with four alternative answers. The research method used is Quasi Experimental Design with the research design of Nonequivalent Control Group Design. Based on the results of the analysis, the researcher can conclude as follows: in the results of the hypothesis test (t test) the results of t count 5.875 t table of 2.055 at 5% significant means 5.875> t table = 2.055 On the basis of these calculations, the alternative hypothesis (Ha) which reads